Is this just sadness or depression symptoms? The emotional condition of junior high school students = Smutek dojrzewania czy objawy depresji? Kondycja emocjonalna gimnazjalistów - Szaban, Dorota; Trzop, Beata (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of this article is to investigate the conditions for depression syndromes among junior high school pupils from the Lubuskie and Wielkopolskie Voievodships and to diagnose their emotional condition. The authors refer to T. Parsons? concept, according to which, health is as an optimal ability to fulfill social roles and expectations imposed by the environment. In this context, puberty and attending junior high school constitute a huge challenge and an experimental field for teenagers, which affects self-assessment of their mental health and emotional condition. Most mental health disorders result from the processes of growing up. The empirical basis for the undertaken considerations are the results of questionnaire surveys conducted in the spring of 2017.
Keywords: mental health; youth; depression; depression masks; zdrowie psychiczne; młodzież; depresja; maski depresyjne